A novel type of Co-Ti-Cr-base γ/γ′ superalloys with low mass density - Zenk, Christopher; Povstugar, Ivan; Li, Rui; Rinaldi, Fernando; Neumeier, Steffen; Raabe, Dierk; Göken, Mathias (Acta Materialia, 2017)
A gamma' strengthened Co-Ti-Cr superalloy is presented with a mass density similar to 14 % below that of typical Co-Al-W-based alloys. The lattice misfit is sufficiently low to form coherent cuboidal gamma' precipitates. Atom probe tomography shows that Cr partitions to the gamma phase, but increases the gamma' volume fraction compared to a binary Co-Ti alloy to more than 60 %. The solubility of Cr in the gamma' phase is significantly higher than expected from previously published values. The gamma' solvus temperature is above 1100 degrees C. The yield strength shows a distinct increase above 600 degrees C surpassing that of Co-9Al-8W (at.%) and conventional Co-base superalloys, even more so when it is normalized by the mass density. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Co-base superalloys; Atom probe tomography (APT); High-temperature deformation; X-ray diffraction (XRD); Phase diagram calculation